Pemikiran Etika Perang ImÄm al-ShawkÄnÄ«: Analisis Teori Just War dan Relevansi Konflik Israel-Palestina: ImÄm al-ShawkÄnÄ«'s Thoughts on War Ethics: An Analysis of the Just War Theory and the Relevance of the Israel-Palestine Conflict - Rizaka, Maghza; Muhid, Muhid; Nurita, Andris; Badi', Syamsul; Kharmain, Muhammad Miftah (Tasfiyah: Jurnal Pemikiran Islam, 2024)
This research analyzes ImÄm al-ShawkÄnÄ«â€™s thoughts on war ethics within the Just War theory perspective, using the book â€œNayl al-Awá¹Är.â€ The Israel-Palestine conflict is seen as an example of the abuse of power in just war ethics to the detriment of Palestinian civilians. Just War theory emphasises justice, proportionality and protection of civilians, yet Israel's military operations often violate these principles. ImÄm al-ShawkÄnÄ«'s thought in Nayl al-Awá¹Är had an Islamic perspective that emphasised justice and humanity in war. Integrating Just War principles with al-ShawkÄnÄ«'s ethics of war can provide a strong ethical framework to evaluate military actions in the Israel-Palestine conflict and seek a more just solution. Through a library research method and descriptive analysis, this study aims to contribute to the explanation of the connection between religion, ethics, and armed conflict, while promoting international peace and justice. Its practical implications highlight the significance of strengthening Islamic values in facing foreign cultural dominance, while its contemporary relevance underscores the necessity of upholding international law and human rights conventions in addressing armed conflicts. Thus, this research not only provides new insights into the ethics of war in Islam but also highlights the importance of actions to uphold humanity and justice in global armed conflicts.